Road traffic deaths in Kashan region, Iran: An eight-year study (2006–2013) - Mahdian, Mehrdad (Chin J Traumatol, 2018)
PURPOSE: The aim of this study was to analyze the trend of road traffic fatalities in Kashan Region, Iran, in a period of eight years. METHODS: Through a cross-sectional study, all road traffic deaths classified under the V01—V99 codes according to ICD-10 in Kashan region, central Iran, from March 2006 to March 2013 and population data were collected from the registration system of Kashan University of Medical Sciences. Years of lost life (YLL) and mortality rates were calculated regarding age, gender and year of the accident. Generalized linear model (GLM) with Poisson log-linear link was used to evaluate the effects of the mentioned variables on mortality rate. RESULTS: During the period of the study (8 years), 928 people (767 men) died due to road traffic injuries (RTIs). The total YLL was 20,818. The mortality rate due to RTIs has been declined constantly from 43.1 in March 2006 to 21.1 per 100,000 in March 2013. The highest mortality rate was found in the age group of over 60 years old and the lowest in the age group of 0–14 years old. Both mortality rate and YLL was greater in men than in women. Poisson regression showed that age, gender and year of the accidents had a significant effect on mortality rate (p < 0.001). CONCLUSION: Although there has been a constant decline of mortality rate in Kashan area within the study period, the value remains higher than the mean level of Eastern Mediterranean region and the global average, which is a notable fact for policymakers and authorities.